Exploring the Gap Between Needs and Practice in Facilitating Breastfeeding Within the Neonatal Intensive Care Setting: An Italian Survey on Organizational Factors - Tambani, Elisabetta; Giannì, Maria Lorella; Bezze, Elena Nicoletta; Sannino, Patrizio; Sorrentino, Gabriele; Plevani, Laura; Morniroli, Daniela; Mosca, Fabio (Frontiers in Pediatrics, 2019)
Introduction: The system-level factors of the neonatal intensive care unit work environment contribute to breastfeeding promotion in the preterm population. The aim of this study was to investigate the operative policies related to breastfeeding support in a sample of Italian Neonatal Intensive Care Units. Materials and Methods: A multicentre cross-sectional survey was conducted, including a sample of 17 head nurses. The items of the questionnaire investigated the following areas: breastfeeding policies, staff education, family centered care and breastfeeding promotion and support both in the neonatal intensive care units and after discharge. Results: Written breastfeeding policies were available for staff in all the neonatal intensive care units, most commonly addressing procedures related to skin-to-skin contact, human milk expression and preterm infant breastfeeding. Most of the neonatal intensive care units correctly advised the mothers to initiate milk expression within six hours from delivery and to pump milk at least six times/day. Breastfeeding training for the nursing staff was planned in the majority of the neonatal intensive care units although according to different schedules. With regard to the family centered care implementation, time restrictions were present in seven neonatal intensive care units, mostly occurring during the night shift and the morning hours concomitantly with medical rounds. Moreover, in the majority of the investigated neonatal intensive care units, the parents were asked to leave the ward when their infant underwent a major invasive procedure or during the nurse/physician shift change report. With regard to breastfeeding promotion and support, eight neonatal care units had a multidisciplinary team with several health care professionals and ten provided information about community-based support services. Most of the units assessed breastfeeding after discharge. Conclusion: Based on the present findings, enrolled Neonatal Intensive Care Units appear to provide breastfeeding-supportive environments with special regard to breastfeeding policies, milk expression practices, interprofessional collaboration and continuity of care. Health care professionals should exert efforts to ensure continuous and updated breastfeeding staff education and promote parent-infant closeness and family centered care.